AKAP6 orchestrates the nuclear envelope microtubule-organizing center by linking golgi and nucleus via AKAP9 - Vergarajauregui, Silvia; Becker, Robert; Steffen, Ulrike; Sharkova, Maria; Esser, Tilman; Petzold, Jana; Billing, Florian; Kapiloff, Michael S.; Schett, Georg; Thievessen, Ingo; Engel, Felix (eLife, 2020)
The switch from centrosomal microtubule-organizing centers (MTOCs) to noncentrosomal MTOCs during differentiation is poorly understood. Here, we identify AKAP6 as key component of the nuclear envelope MTOC. In rat cardiomyocytes, AKAP6 anchors centrosomal proteins to the nuclear envelope through its spectrin repeats, acting as an adaptor between nesprin-1 alpha and Pcnt or AKAP9. In addition, AKAP6 and AKAP9 form a protein platform tethering the Golgi to the nucleus. Both Golgi and nuclear envelope exhibit MTOC activity utilizing either AKAP9, or Pcnt-AKAP9, respectively. AKAP6 is also required for formation and activity of the nuclear envelope MTOC in human osteoclasts. Moreover, ectopic expression of AKAP6 in epithelial cells is sufficient to recruit endogenous centrosomal proteins. Finally, AKAP6 is required for cardiomyocyte hypertrophy and osteoclast bone resorption activity. Collectively, we decipher the MTOC at the nuclear envelope as a bi-layered structure generating two pools of microtubules with AKAP6 as a key organizer.
CRIS-Team WoS Importer:2021-01-01

A New Printable Alginate/Hyaluronic Acid/Gelatin Hydrogel Suitable for Biofabrication of In Vitro and In Vivo Metastatic Melanoma Models - Schmid, Rafael; Schmidt, Sonja; Detsch, Rainer; Horder, Hannes; Blunk, Torsten; Schrüfer, Stefan; Schubert, Dirk W.; Fischer, Lena; Thievessen, Ingo; Heltmann-Meyer, Stefanie; Steiner, Dominik; Schneidereit, Dominik; et al. (Advanced Functional Materials, 2022)
Two-dimensional (2D) cancer models have been the standard for drug development over the past few years, but they frequently do not resemble in vivo properties adequately. 3D models are superior in many aspects and are, therefore, more similar to human pathophysiology. Over the past years, the emerging field of biofabrication has made significant advances, resulting in even more sophisticated 3D models. With this study, a hydrogel is created for biofabrication that is suitable for mimicking the tumor microenvironment in vitro and is further tested as a new vascularized melanoma model in vivo. The alginate/hyaluronic acid/gelatin bioink shows good shape-fidelity, high cell survival rates, and enables successful cultivation of melanoma cells and adipose-derived stem cells as well as cell differentiation in vitro. In vivo, in the arteriovenous loop model, it proves to be a unique method to study melanoma progression, tumor vascularization, and ultimately and reliably metastases in an isolated and controlled environment. These results show that this 3D model is very application-oriented for molecular research and therapy development.
CRIS-Team Scopus Importer:2021-10-22
Keywords: bioinks; metastasis; stem cells; tissue engineering; tumors

A One-Pot Universal Approach to Fabricate Lubricant-Infused Slippery Surfaces on Solid Substrates - Tesler, Alexander; Prado, Lucia; Khusniyarov, Marat; Thievessen, Ingo; Mazare, Anca Valentina; Fischer, Lena; Virtanen, Sannakaisa; Goldmann, Wolfgang; Schmuki, Patrik (Advanced Functional Materials, 2021)
Wetting is a surface phenomenon that commonly occurs in nature and has an enormous influence on human life. Slippery liquid-infused porous surfaces have recently been developed to support the growing demand for anti-fouling coatings. While short-chain fluorinated compounds, commonly used to reduce the surface energy of substrates, are banned due to environmental toxicity, silane-based compounds are expensive and barely scalable. In this sense, silicone-based chemistry may match the gap as a real alternative. However, the grafting approaches demonstrated so far suffered from either slow binding kinetics or are applied under harsh conditions. Here, it is demonstrated that polydimethylsiloxanes graft to virtually any substrate when illuminated by UV light serving simultaneously as a reducing surface energy agent and infusing lubricant. This procedure is applied on metals, metal oxides, and ceramics of various surface morphologies. The proposed approach is simple, fast, scalable, environmentally friendly, and of low-cost, yet forms stable lubricant-infused slippery surfaces by a one-pot process. Due to the biocompatibility of silicone-based compounds, the process is examined on plain medically applicable substrates such as scalpel blades and glass lenses that display enhanced corrosion resistance, reduced friction through incision, and repel blood staining and bacterial adhesion without deteriorating their mechanical and optical characteristics.
CRIS-Team Scopus Importer:2021-05-14
Keywords: anti-biofouling; blood-repellent coating; corrosion resistance; lubricant-infused slippery surfaces; polydimethylsiloxane

Calcium supplementation of bioinks reduces shear stress-induced cell damage during bioprinting - Fischer, Lena; Nosratlo, Mojtaba; Hast, Katharina; Karakaya, Emine; Ströhlein, Nadi; Esser, Tilman; Gerum, Richard; Richter, Sebastian; Engel, Felix; Detsch, Rainer; Fabry, Ben; Thievessen, Ingo (Biofabrication, 2022)
During bioprinting, cells are suspended in a viscous bioink and extruded under pressure through small diameter printing needles. The combination of high pressure and small needle diameter exposes cells to considerable shear stress, which can lead to cell damage and death. Approaches to monitor and control shear stress-induced cell damage are currently not well established. To visualize the effects of printing-induced shear stress on plasma membrane integrity, we add FM 1-43 to the bioink, a styryl dye that becomes fluorescent when bound to lipid membranes, such as the cellular plasma membrane. Upon plasma membrane disruption, the dye enters the cell and also stains intracellular membranes. Extrusion of alginate-suspended NIH/3T3 cells through a 200 mu m printing needle led to an increased FM 1-43 incorporation at high pressure, demonstrating that typical shear stresses during bioprinting can transiently damage the plasma membrane. Cell imaging in a microfluidic channel confirmed that FM 1-43 incorporation is caused by cell strain. Notably, high printing pressure also impaired cell survival in bioprinting experiments. Using cell types of different stiffnesses, we find that shear stress-induced cell strain, FM 1-43 incorporation and cell death were reduced in stiffer compared to softer cell types and demonstrate that cell damage and death correlate with shear stress-induced cell deformation. Importantly, supplementation of the suspension medium with physiological concentrations of CaCl2 greatly reduced shear stress-induced cell damage and death but not cell deformation. As the sudden influx of calcium ions is known to induce rapid cellular vesicle exocytosis and subsequent actin polymerization in the cell cortex, we hypothesize that calcium supplementation facilitates the rapid resealing of plasma membrane damage sites. We recommend that bioinks should be routinely supplemented with physiological concentrations of calcium ions to reduce shear stress-induced cell damage and death during extrusion bioprinting.
CRIS-Team WoS Importer:2022-08-26

From Thermogelling Hydrogels toward Functional Bioinks: Controlled Modification and Cytocompatible Crosslinking - Hahn, Lukas; Beudert, Matthias; Gutmann, Marcus; Kessler, Larissa; Stahlhut, Philipp; Fischer, Lena; Karakaya, Emine; Lorson, Thomas; Thievessen, Ingo; Detsch, Rainer; Luehmann, Tessa; Luxenhofer, Robert (Macromolecular Bioscience, 2021)
Hydrogels are key components in bioink formulations to ensure printability and stability in biofabrication. In this study, a well-known Diels-Alder two-step post-polymerization modification approach is introduced into thermogelling diblock copolymers, comprising poly(2-methyl-2-oxazoline) and thermoresponsive poly(2-n-propyl-2-oxazine). The diblock copolymers are partially hydrolyzed and subsequently modified by acid/amine coupling with furan and maleimide moieties. While the thermogelling and shear-thinning properties allow excellent printability, trigger-less cell-friendly Diels-Alder click-chemistry yields long-term shape-fidelity. The introduced platform enables easy incorporation of cell-binding moieties (RGD-peptide) for cellular interaction. The hydrogel is functionalized with RGD-peptides using thiol-maleimide chemistry and cell proliferation as well as morphology of fibroblasts seeded on top of the hydrogels confirm the cell adhesion facilitated by the peptides. Finally, bioink formulations are tested for biocompatibility by incorporating fibroblasts homogenously inside the polymer solution pre-printing. After the printing and crosslinking process good cytocompatibility is confirmed. The established bioink system combines a two-step approach by physical precursor gelation followed by an additional chemical stabilization, offering a broad versatility for further biomechanical adaptation or bioresponsive peptide modification.
CRIS-Team Scopus Importer:2021-08-06
Keywords: biofabrication; bioprinting; chemical crosslinking; hydrogels

FUCCI Reporter Gene-Based Cell Cycle Analysis - Fischer, Lena; Thievessen, Ingo (Humana Press Inc., 2023)
One of the most commonly assessed parameters in cellular analyses is the proliferative activity of a cell population. The fluorescence ubiquitin cell cycle indicator (FUCCI)-based system allows live and in vivo observation of cell cycle progression. Based on the mutually exclusive activity of two fluorescently labeled proteins cdt1 and geminin during the G0/1 and S/G2/M phases of the cell cycle, individual cells can be assigned to their respective cell cycle phase by fluorescence imaging of the nucleus. Here, we describe the generation of NIH/3T3 cells containing the FUCCI reporter system by lentiviral transduction and their use in 3D culture assays. The protocol can be adapted to other cell lines.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Cdt1; Cell cycle analysis; Cell proliferation; FUCCI; Geminin; Lentivirus

Functional genomics meta-analysis to identify gene set enrichment networks in cardiac hypertrophy - Angeloni, Miriam; Thievessen, Ingo; Engel, Felix; Magni, Paolo; Ferrazzi, Fulvia (Biological Chemistry, 2021)
In order to take advantage of the continuously increasing number of transcriptome studies, it is important to develop strategies that integrate multiple expression datasets addressing the same biological question to allow a robust analysis. Here, we propose a meta-analysis framework that integrates enriched pathways identified through the Gene Set Enrichment Analysis (GSEA) approach and calculates for each meta-pathway an empirical p-value. Validation of our approach on benchmark datasets showed comparable or even better performance than existing methods and an increase in robustness with increasing number of integrated datasets. We then applied the meta-analysis framework to 15 functional genomics datasets of physiological and pathological cardiac hypertrophy. Within these datasets we grouped expression sets measured at time points that represent the same hallmarks of heart tissue remodeling ('aggregated time points') and performed meta-analysis on the expression sets assigned to each aggregated time point. To facilitate biological interpretation, results were visualized as gene set enrichment networks. Here, our meta-analysis framework identified well-known biological mechanisms associated with pathological cardiac hypertrophy (e.g., cardiomyocyte apoptosis, cardiac contractile dysfunction, and alteration in energy metabolism). In addition, results highlighted novel, potentially cardioprotective mechanisms in physiological cardiac hypertrophy involving the down-regulation of immune cell response, which are worth further investigation.
CRIS-Team Scopus Importer:2021-06-11
Keywords: cardiac hypertrophy; pathological hypertrophy; pathway network; physiological hypertrophy; transcriptome meta-analysis

Long-term stability of aerophilic metallic surfaces underwater - Tesler, Alexander; Kolle, Stefan; Prado, Lucia; Thievessen, Ingo; Böhringer, David; Backholm, Matilda; Karunakaran, Bhuvaneshwari; Nurmi, Heikki A.; Latikka, Mika; Fischer, Lena; Stafslien, Shane; Cenev, Zoran M.; et al. (Nature Materials, 2023)
Aerophilic surfaces immersed underwater trap films of air known as plastrons. Plastrons have typically been considered impractical for underwater engineering applications due to their metastable performance. Here, we describe aerophilic titanium alloy (Ti) surfaces with extended plastron lifetimes that are conserved for months underwater. Long-term stability is achieved by the formation of highly rough hierarchically structured surfaces via electrochemical anodization combined with a low-surface-energy coating produced by a fluorinated surfactant. Aerophilic Ti surfaces drastically reduce blood adhesion and, when submerged in water, prevent adhesion of bacteria and marine organisms such as barnacles and mussels. Overall, we demonstrate a general strategy to achieve the long-term stability of plastrons on aerophilic surfaces for previously unattainable underwater applications.
CRIS-Team Scopus Importer:2023-09-29

Molecular changes induced in melanoma by cell culturing in 3D alginate hydrogels - Kappelmann-Fenzl, M.; Schmidt, Sonja; Fischer, Stefan; Schmid, Rafael; Lämmerhirt, Lisa; Fischer, Lena; Schrüfer, Stefan; Thievessen, Ingo; Schubert, Dirk W.; Matthies, Alexander Oliver; Detsch, Rainer; Boccaccini, Aldo R.; et al. (Cancers, 2021)
Alginate hydrogels have been used as a biomaterial for 3D culturing for several years. Here, gene expression patterns in melanoma cells cultivated in 3D alginate are compared to 2D cultures. It is well-known that 2D cell culture is not resembling the complex in vivo situation well. However, the use of very intricate 3D models does not allow performing high-throughput screening and analysis is highly complex. 3D cell culture strategies in hydrogels will better mimic the in vivo situation while they maintain feasibility for large-scale analysis. As alginate is an easy-to-use material and due to its favorable properties, it is commonly applied as a bioink component in the growing field of cell encapsulation and biofabrication. Yet, only a little information about the transcriptome in 3D cultures in hydrogels like alginate is available. In this study, changes in the transcriptome based on RNA-Seq data by cultivating melanoma cells in 3D alginate are analyzed and reveal marked changes compared to cells cultured on usual 2D tissue culture plastic. Deregulated genes represent valuable cues to signaling pathways and molecules affected by the culture method. Using this as a model system for tumor cell plasticity and heterogeneity, EGR1 is determined to play an important role in melanoma progression.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 3D cultivation; Biomaterials; EGR1; Melanoma; Whole transcriptome

Nontoxic Liquid-Infused Slippery Coating Prepared on Steel Substrates Inhibits Corrosion and Biofouling Adhesion - Tesler, Alexander; Prado, Lucia; Thievessen, Ingo; Mazare, Anca Valentina; Schmuki, Patrik; Virtanen, Sannakaisa; Goldmann, Wolfgang (ACS Applied Materials and Interfaces, 2022)
Wetting of surfaces plays a vital role in many biological and industrial processes. There are several phenomena closely related to wetting such as biofouling and corrosion that cause the deterioration of materials, while the efforts to prevent the degradation of surface functionality have spread over several millennia. Antifouling coatings have been developed to prevent/delay both corrosion and biofouling, but the problems remain unsolved, influencing the everyday life of the modern society in terms of safety and expenses. In this study, liquid-infused slippery surfaces (LISSs), a recently developed nontoxic repellent technology, that is, a flat variation of omniphobic slippery liquid-infused porous surfaces (SLIPSs), were studied for their anti-corrosion and marine anti-biofouling characteristics on metallic substrates under damaged and plain undamaged conditions. Austenitic stainless steel was chosen as a model due to its wide application in aquatic environments. Our LISS coating effectively prevents biofouling adhesion and decays corrosion of metallic surfaces even if they are severely damaged. The mechanically robust LISS reported in this study significantly extends the SLIPS technology, prompting their application in the marine environment due to the synergy between the facile fabrication process, rapid binding kinetics, nontoxic, ecofriendly, and low-cost applied materials together with excellent repellent characteristics.
CRIS-Team Scopus Importer:2022-07-08
Keywords: algae; anti-biofouling coating; biofilms; corrosion resistance; diatoms; liquid-infused slippery surfaces; polydimethylsiloxane

Partner, Neighbor, Housekeeper and Dimension: 3D versus 2D Glomerular Co-Cultures Reveal Drawbacks of Currently Used Cell Culture Models - Rederer, Anna; Rose, Victoria; Krüger, René; Schmittutz, Linda; Swierzy, Izabela; Fischer, Lena; Thievessen, Ingo; Bauer, Julian; Friedrich, Oliver; Schiffer, Mario; Müller-Deile, Janina (International Journal of Molecular Sciences, 2023)
Signaling-pathway analyses and the investigation of gene responses to different stimuli are usually performed in 2D monocultures. However, within the glomerulus, cells grow in 3D and are involved in direct and paracrine interactions with different glomerular cell types. Thus, the results from 2D monoculture experiments must be taken with caution. We cultured glomerular endothelial cells, podocytes and mesangial cells in 2D/3D monocultures and 2D/3D co-cultures and analyzed cell survival, self-assembly, gene expression, cell–cell interaction, and gene pathways using live/dead assay, time-lapse analysis, bulk-RNA sequencing, qPCR, and immunofluorescence staining. Without any need for scaffolds, 3D glomerular co-cultures self-organized into spheroids. Podocyte- and glomerular endothelial cell-specific markers and the extracellular matrix were increased in 3D co-cultures compared to 2D co-cultures. Housekeeping genes must be chosen wisely, as many genes used for the normalization of gene expression were themselves affected in 3D culture conditions. The transport of podocyte-derived VEGFA to glomerular endothelial cells confirmed intercellular crosstalk in the 3D co-culture models. The enhanced expression of genes important for glomerular function in 3D, compared to 2D, questions the reliability of currently used 2D monocultures. Hence, glomerular 3D co-cultures might be more suitable in the study of intercellular communication, disease modelling and drug screening ex vivo.
Created from Fastlane, Scopus look-up
Keywords: 3D co-culture; bulk-RNA sequencing; cell culture model; cell matrix; cell–cell communication; glomerular spheroids

PCL micro-dumbbells - A new class of polymeric particles reveals morphological biofunctionality - Sonnleitner, David; Schaefer, Natascha; Wieland, Annalena; Fischer, Lena; Pasberg, Patrick; Thievessen, Ingo; Lang, Gregor (Applied Materials Today, 2021)
Biopolymeric particles can be fibrous or spherical, highly determining their areas of medical applications such as biomimetic fibers for tissue engineering or injectable capsules. In this work, we present a completely novel morphology, combining structural features of fibers and spheres in dumbbell-shaped Poly-epsilon-Caprolactone (PCL) micro-particles. Strikingly, such complex structures could be achieved by simply balancing out the parameters of a standard electrospinning setup together with fine-tuned spinning dope compositions. In-situ entropy-elastic snapping of deposited fibers could be triggered by combining PCL with different molecular weights, allowing for control over the aspect ratio of generated dumbbells in an accurate manner. With a single electrospinning nozzle, high production rates in the range of 80.000 dumbbells per second were achieved. To assess morphologically induced biofunctionality, dumbbell suspending and surface modification with collagen was performed and in vitro-testing with U87 reporter cells demonstrated significantly enhanced integrin-based cell adhesion on PCL-dumbbells as compared to continuous PCL-fibers. The results clearly unravel the remarkable potential of such structures in the field of tissue engineering. Revealing this new class of polymeric particles will also open the door to various new approaches including injectables, biofabrication and cosmetics, moreover, defining a novel type of filler material. (C) 2021 The Authors. Published by Elsevier Ltd.
CRIS-Team WoS Importer:2021-09-24

pyTFM: A tool for traction force and monolayer stress microscopy - Bauer, Andreas; Prechová, Magdalena; Fischer, Lena; Thievessen, Ingo; Gregor, Martin; Fabry, Ben (PLoS Computational Biology, 2021)
Cellular force generation and force transmission are of fundamental importance for numerous biological processes and can be studied with the methods of Traction Force Microscopy (TFM) and Monolayer Stress Microscopy. Traction Force Microscopy and Monolayer Stress Microscopy solve the inverse problem of reconstructing cell-matrix tractions and inter- and intra-cellular stresses from the measured cell force-induced deformations of an adhesive substrate with known elasticity. Although several laboratories have developed software for Traction Force Microscopy and Monolayer Stress Microscopy computations, there is currently no software package available that allows non-expert users to perform a full evaluation of such experiments. Here we present pyTFM, a tool to perform Traction Force Microscopy and Monolayer Stress Microscopy on cell patches and cell layers grown in a 2-dimensional environment. pyTFM was optimized for ease-of-use; it is open-source and well documented (hosted at https://pytfm.readthedocs.io/) including usage examples and explanations of the theoretical background. pyTFM can be used as a standalone Python package or as an add-on to the image annotation tool ClickPoints. In combination with the ClickPoints environment, pyTFM allows the user to set all necessary analysis parameters, select regions of interest, examine the input data and intermediary results, and calculate a wide range of parameters describing forces, stresses, and their distribution. In this work, we also thoroughly analyze the accuracy and performance of the Traction Force Microscopy and Monolayer Stress Microscopy algorithms of pyTFM using synthetic and experimental data from epithelial cell patches.
CRIS-Team Scopus Importer:2021-07-09

Role of Fiber Thickness and Surface Treatment of Electrospun Polycaprolactone Matrices on the Growth of Different Breast Cancer‐Associated Cells - Sivakumar, Sankaranarayanan; Schmid, Rafael; Wieland, Annalena; Strissel, Pamela; Strick, Reiner; Fischer, Lena; Thievessen, Ingo; Kataev, Elmar; Arkudas, Andreas; Horch, Raymund E.; Schubert, Dirk W.; Kengelbach-Weigand, Annika (Advanced Materials Interfaces, 2022)
Cancer models mimicking the tumor microenvironment are necessary to successfully develop and predict responses of oncological drugs. In this study, electrospun polycaprolactone (PCL) matrices are tested for the development of an in vitro breast cancer model. The effects of fiber thickness and plasma-treatment of the matrices on in vitro growth of breast cancer-associated cells, namely breast cancer cells MDA-MB-231, primary adipose-derived stem cells (ADSCs) and primary endothelial progenitor cells (EPCs) are evaluated. Surface treatment of the matrices by air-plasma leads to increased oxygen/carbon ratio and hydrophilicity. WST-8 analysis reveals that the proliferation of all three cell types increased exponentially over 12 d on all matrices. MDA-MB-231 and ADSC show a higher proliferation on nanofibers due to enhanced cellular adhesion compared to microfibers. In contrast, EPCs show a significantly higher proliferation on microfibers than on nanofibers at day 12 which can further be significantly improved by air-plasma treatment. Cross-sectioning analysis shows that cells grow on the surface of nanofibers, while microfibers have considerable cellular infiltration. These findings suggest that the electrospun PCL matrices are a suitable tool for the development of breast cancer models containing several cell types, which can ultimately lead to designing novel tumor therapies.<br

The desmin mutation R349P increases contractility and fragility of stem cell-generated muscle micro-tissues - Spörrer, Marina; Kah, Delf-Thorge Eric; Gerum, Richard; Reischl, Barbara; Huraskin, Danyil; Dessalles, Claire A.; Schneider, Werner; Goldmann, Wolfgang; Herrmann, Harald; Thievessen, Ingo; Clemen, Christoph S.; Friedrich, Oliver; et al. (Neuropathology and Applied Neurobiology, 2021)
Aims: Desminopathies comprise hereditary myopathies and cardiomyopathies caused by mutations in the intermediate filament protein desmin that lead to severe and often lethal degeneration of striated muscle tissue. Animal and single cell studies hinted that this degeneration process is associated with massive ultrastructural defects correlating with increased susceptibility of the muscle to acute mechanical stress. The underlying mechanism of mechanical susceptibility, and how muscle degeneration develops over time, however, has remained elusive. Methods: Here, we investigated the effect of a desmin mutation on the formation, differentiation, and contractile function of in vitro-engineered three-dimensional micro-tissues grown from muscle stem cells (satellite cells) isolated from heterozygous R349P desmin knock-in mice. Results: Micro-tissues grown from desmin-mutated cells exhibited spontaneous unsynchronised contractions, higher contractile forces in response to electrical stimulation, and faster force recovery compared with tissues grown from wild-type cells. Within 1 week of culture, the majority of R349P desmin-mutated tissues disintegrated, whereas wild-type tissues remained intact over at least three weeks. Moreover, under tetanic stimulation lasting less than 5 s, desmin-mutated tissues partially or completely ruptured, whereas wild-type tissues did not display signs of damage. Conclusions: Our results demonstrate that the progressive degeneration of desmin-mutated micro-tissues is closely linked to extracellular matrix fibre breakage associated with increased contractile forces and unevenly distributed tensile stress. This suggests that the age-related degeneration of skeletal and cardiac muscle in patients suffering from desminopathies may be similarly exacerbated by mechanical damage from high-intensity muscle contractions. We conclude that micro-tissues may provide a valuable tool for studying the organization of myocytes and the pathogenic mechanisms of myopathies.
CRIS-Team Scopus Importer:2021-12-17
Keywords: desmin; desminopathy; micro-tissue; skeletal muscle physiology; tissue engineering

The focal adhesion protein β-parvin controls cardiomyocyte shape and sarcomere assembly in response to mechanical load - Thievessen, Ingo; Suhr, Frank; Vergarajauregui, Silvia; Böttcher, Ralph T.; Brixius, Klara; Rosenberger, Georg; Fleischmann, Bernd K.; Ghanem, Alexander; Krüger, Marcus; Engel, Felix; Fabry, Ben; Bloch, Wilhelm; et al. (Current Biology, 2022)
Physiological and pathological cardiac stress induced by exercise and hypertension, respectively, increase the hemodynamic load for the heart and trigger specific hypertrophic signals in cardiomyocytes leading to adaptive or maladaptive cardiac hypertrophy responses involving a mechanosensitive remodeling of the contractile cytoskeleton. Integrins sense load and have been implicated in cardiac hypertrophy, but how they discriminate between the two types of cardiac stress and translate mechanical loads into specific cytoskeletal signaling pathways is not clear. Here, we report that the focal adhesion protein β-parvin is highly expressed in cardiomyocytes and facilitates the formation of cell protrusions, the serial assembly of newly synthesized sarcomeres, and the hypertrophic growth of neonatal rat ventricular cardiomyocytes (NRVCs) in vitro. In addition, physiological mechanical loading of NRVCs by either the application of cyclic, uni-axial stretch, or culture on physiologically stiff substrates promotes NRVC elongation in a β-parvin-dependent manner, which is achieved by binding of β-parvin to α/β-PIX, which in turn activates Rac1. Importantly, loss-of-function studies in mice also revealed that β-parvin is essential for the exercise-induced cardiac hypertrophy response in vivo. Our results identify β-parvin as a novel mechano-responsive signaling hub in hypertrophic cardiomyocytes that drives cell elongation in response to physiological mechanical loads.
CRIS-Team Scopus Importer:2022-08-05
Keywords: affixin; cardiac hypertrophy; integrin-linked kinase; mechanotransduction; Rac1; sarcomere assembly; β-parvin

Three-dimensional force microscopy of cells in biopolymer networks - Steinwachs, Julian; Metzner, Claus; Skodzek, Kai; Lang, Nadine; Thievessen, Ingo; Mark, Christoph; Münster, Stefan; Aifantis, Katerina E.; Fabry, Ben (Nature Methods, 2016)

Treatment of keratinocytes with 4-phenylbutyrate in epidermolysis bullosa: Lessons for therapies in keratin disorders - Spörrer, Marina; Prochnicki, Ania; Tölle, Regine C.; Nyström, Alexander; Esser, Philipp R.; Homberg, Melanie; Athanasiou, Ioannis; Zingkou, Eleni; Schilling, Achim; Gerum, Richard; Thievessen, Ingo; Winter, Lilli; et al. (EBioMedicine, 2019)
Background: Missense mutations in keratin 5 and 14 genes cause the severe skin fragility disorder epidermolysis bullosa simplex (EBS)by collapsing of the keratin cytoskeleton into cytoplasmic protein aggregates. Despite intense efforts, no molecular therapies are available, mostly due to the complex phenotype of EBS, comprising cell fragility, diminished adhesion, skin inflammation and itch. Methods: We extensively characterized KRT5 and KRT14 mutant keratinocytes from patients with severe generalized EBS following exposure to the chemical chaperone 4-phenylbutyrate (4-PBA). Findings: 4-PBA diminished keratin aggregates within EBS cells and ameliorated their inflammatory phenotype. Chemoproteomics of 4-PBA-treated and untreated EBS cells revealed reduced IL1β expression- but also showed activation of Wnt/β-catenin and NF-kB pathways. The abundance of extracellular matrix and cytoskeletal proteins was significantly altered, coinciding with diminished keratinocyte adhesion and migration in a 4-PBA dose-dependent manner. Interpretation: Together, our study reveals a complex interplay of benefits and disadvantages that challenge the use of 4-PBA in skin fragility disorders.
CRIS-Team Scopus Importer:2019-05-17
Keywords: 4-PBA; Epidermolysis bullosa; Keratinocyte; Keratins; Skin blistering

Vinculin, cell mechanics, and tumor cell invasion - Goldmann, Wolfgang; Auernheimer, Vera; Thievessen, Ingo; Fabry, Ben (Cell Biology International, 2013)

Vinculin is required for cell polarization, migration, and extracellular matrix remodeling in 3D collagen - Thievessen, Ingo; Fakhri, Nikta; Steinwachs, Julian; Kraus, Viola; McIsaac, R. Scott; Gao, Liang; Chen, Bi-Chang; Baird, Michelle A.; Davidson, Michael W.; Betzig, Eric; Oldenbourg, Rudolf; Waterman, Clare M.; et al. (The FASEB Journal, 2015)